1996
DOI: 10.1021/bi952937w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cys115 to Asp Substitution in the Escherichia coli Cell Wall Biosynthetic Enzyme UDP-GlcNAc Enolpyruvyl Transferase (MurA) That Confers Resistance to Inactivation by the Antibiotic Fosfomycin

Abstract: The antibiotic fosfomycin inhibits bacterial cell wall biosynthesis by inactivation of UDP-GlcNAc enolpyruvyl tranferase (MurA). Prior work has established that Cys115 of Escherichia coli and Enterobacter cloacae MurA is the active site nucleophile alkylated by fosfomycin and implicated this residue in the formation of a covalent phospholactyl-enzyme adduct derived from substrate, phosphoenolpyruvate (PEP). On the basis of sequencing information from putative MurA homolog from Mycobacterium tuberculosis, we ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(198 citation statements)
references
References 24 publications
(37 reference statements)
8
188
0
2
Order By: Relevance
“…To distinguish between these possibilities, we took advantage of the fact that fosfomycin producing Mycobacteria possess a MurA that contains an activesite aspartate in place of cysteine. This natural substitution renders the protein resistant to modification by fosfomycin (27), and we also found that it was resistant to alkylation with bromoa- cetate (Fig. S3).…”
Section: Resultsmentioning
confidence: 55%
“…To distinguish between these possibilities, we took advantage of the fact that fosfomycin producing Mycobacteria possess a MurA that contains an activesite aspartate in place of cysteine. This natural substitution renders the protein resistant to modification by fosfomycin (27), and we also found that it was resistant to alkylation with bromoa- cetate (Fig. S3).…”
Section: Resultsmentioning
confidence: 55%
“…The oxacarbenium ion was also supported by site-directed mutagenesis experiments (11). When Cys115 was mutated to Asp, the enzyme lost the ability to be inhibited by fosfomycin.…”
Section: Evidence Of Oxacarbenium Ion In Addition Stepsmentioning
confidence: 95%
“…The reaction mechanisms of both MurA and AroA have been studied intensively with pre-steady state experiments (11,14,15), site directed mutagenesis (11), substrate analogues (16)(17)(18), x-ray crystallography (7,19,20), fluorescence titration (21) and NMR experiments (6,22). Their mechanisms are similar in several aspects.…”
Section: General Acid Base Catalysis and Tetrahedral Intermediatementioning
confidence: 99%
See 2 more Smart Citations